Avaliação da qualidade de vida de indivíduos com carcinoma bem diferenciado de tireoide através do WHOQOL-100 - Furino, Fernanda de Oliveira (2017)
Background: Quality of life (QoL) is a broad construct that encompasses multidimensionality and subjectivity in its definition. This evaluation is being used in the oncological area. Thyroid carcinoma (TC) is one of the types of head and neck carcinomas that affect QoL. The differentiated thyroid carcinoma (DTC) subtype comprises most cases. Total thyroidectomy is the chosen surgery in cases of DTC and some benign thyroid pathology. DTC treatment includes, in addition to surgery, radioiodine therapy and suppressive doses of levothyroxine. Although it is a carcinoma with an excellent prognosis, the impact of the diagnosis, the complexity of the treatment, clinical follow-up and the risk of recurrence may lead negative impacts on QoL. Objective: To evaluate the QoL of patients treated of DTC using the WHOQOL-100 questionnaire. Methodology: This study had a quantitative, descriptive cross-sectional design. 300 individuals were evaluated and divided into the following groups: thyroid carcinoma (CaT), benign pathologies (PB) and control (C). Their QoL was measured using the WHOQOL-100 self-administered instrument. In the descriptive analysis, the categorical data were represented in absolute and relative frequencies and the numerical ones in average, standard deviation and standard error. The differences between averages of the quantitative variables were evaluated using the Kruskal-Wallis test and Dunn post-test, with a significance of 5%. Statistical analysis was performed using GraphPad prism 5® software. The evaluation of the interaction between the variables was conducted through stratified and multivariate analyzes (multiple correlation). The value of the regression parameter was defined as > 0.3 indicating a significant correlation value. Results: The domains that presented significantly reduced scores in CaT ≤ 45 years individuals were: physical health (p = 0.0115) in relation to group C; level of independence (p <0.0001) in relation to group C; The domain that presented a significantly increased score in CaT subjects ≤ 45 years was: environmental (p = 0.0064) in relation to groups C and PB. In the age range > 45 years, the domains that presented a significantly increased score in the CaT group were: environment (p = 0.0003) in relation to group C; Global QoL (p = 0.0129) in relation to group C. There were no significant differences in the psychological, social relations and spirituality domains between the groups. These results add to the existing literature new and recent knowledge about QoL in DTC patients, such as the finding of improvement in overall QoL in patients with DTC > 45 years; negative repercussion of the DTC on the physical health and level of independence domains in younger patients; importance of spirituality in Brazilian culture; higher scores in the environment domain in all ages of the individuals with DTC, which may reflect the success of programs designed to provide social and financial support to these patients. Discussion and conclusion: The adoption of some of the measures which may have important repercussions for the clinical practice are: actions that improve the patients' daily life should be adopted, such as the stimulating the practice of physical activity, follow-up and psychological support throughout the treatment for patients and their families, providing appropriate guidelines on the DTC and its treatment, as well as health promotion and awareness initiatives on DTC for the general population, individualized and agreed upon treatment with all the actors involved in patient care and provide adequate orientation about the rights of the patient with DTC, in order to ensure these individuals the opportunity to enjoy all the benefits guaranteed by Brazilian legislation.